Eurasian Economic Union: A Regional Economic Hegemony Initiative - YILMAZ, Serdar (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
It can be assumed that international relations terminology has not mentioned enough about the significance of the Eurasian Economic Union in territorial as well as in economic terms during a period of growing geopolitical risks and high interdependence between the member countries and the rest. According to Kazakhstan’s President Nursultan Nazarbayev, it is truly difficult for states to overcome economic, political and security issues and therefore, states need to act together against the problems in a globalizing world by establishing regional and international organisations. This article thus examines the Eurasian Economic Union integration proces, which is driven by political and economic factors that consolidate regional security and create an effective economic system, whether it in the long term will become successful or not. The author also analyses the Kazakh economic and strategic interests in the region as well as the motivation, power and influence of other members in deepening the cooperation with international arena and the limits in the economic-security integration.